Going Home - Shuck, Kim (Transmotion, 2015)
The notion that 'you can never go home again' may well be true for some. When examined through the lens of an hyphenate Ani yun wiya identity, however, it may become clear that some will find themselves at home, some may work to get home, but either way respect requires allowing home to be what it has become. After the last five hundred years, the changes of a handful of decades are hardly a game ender. Even in this altered light home might recognize the traveler.